Hemodynamic Picture After Spinal Anesthesia Sectio Caesarea - Fredy, Fredy Marta; Triyudono, Danang; Sebayang, Septian; Suandika, Made (Global Indonesia Health Care (GOICARE), 2025)
Background: Sectio caesarea is a surgical procedure through an abdominal and uterine wall incision to remove the fetus, placenta and amniotic fluid. SC action with spinal anesthesia has an impact on body hemodynamics, such as changes in blood pressure, changes in pulse rate and changes in MAP. Purpose: The purpose of this research is to document the vital signs of patients undergoing post-spinal anesthesia for sectio secaria surgery at Sriwijaya Hospital Palembang. Methods: Research of this kind is known as descriptive research. This research used a purposeful sampling strategy to select 93 individuals who had spinal anesthesia for a caesarean delivery. Results: The frequency and percentages of blood pressure, pulse, and MAP of pregnant women having spinal acupuncture with anesthesia were determined by univariate data analysis. The majority of the 93 participants who had spinal anesthesia for caesarean section surgery had hypertension (60.2% of the total), asthma (72%) in 67 participants, systolic blood pressure below 90 mmHg in 45 participants (48.38%), and diastolic blood pressure below 60 mmHg in 46.2%. There were 52 cases of tachycardia (55.9% of the total), 33 cases of abnormal heartbeats (35.5% of the total), and 8 cases of brachycardias (8.6% of the total). In terms of population, 80 individuals (86.02%) reported normal levels, whereas 13 (13.98%) reported high levels. Conclusion: The majority of participants who had spinal anesthesia for section caesarian surgery reported abnormal MAP readings, pulse tachycardia, and hypotension.